Da’wah applications in counseling process - Ismail, Zainab; Wan Ahmad, Wan Ibrahim; Ab. Rahman, Asyraf (IDOSI Publications, 2014)
This article discusses some aspects of Islamic missionary applied in the counseling process at the Federal Territory Islamic Religious Department Kuala Lumpur (JAWI), Malaysia.A total of 310 participants from 886 clients at the counseling unit, were selected as respondents.This study found that counselors play a significant role in regards to Islamic missionary since most of the counselors have a degree in Islamic studies. As a counselor for missionary program, they are not only responsible for improving the conflict, but also should give fullest effort in preventing divorce and preserving harmonious environment among st the clients.From the observations on the process of counseling, as well as information from counselors, the study concludes that several approaches employed in the counseling process in parallel with the application of da’wah to emphasis al-amr bi al-ma’ruf wa al-nahy ‘an al-munkar (enjoining the good and forbidding the evil) while dealing with couples with marital problems, include such aspects as Islamic family laws, the rights and responsibility of husband and wife, advantages of patient, prohibition of divorce and advice and instruction.